Conhecimento dos agentes comunitários de saúde sobre a Tuberculose, suas medidas de controle e tratamento diretamente observado - Gustavo Silva Souto Rocha (2014)
Tuberculosis has a strong social component and emphasizing as a public health problem worldwide. The control of this disease remains a current challenge, given the divergence between the rate of cases with outcomes of healing and registered target set to achieve its elimination. Given the goal of reducing treatment dropout among cases of the disease, the strategies recommended by the World Health Organization is the realization of Directly Observed Treatment (DOT). In Brazil, the Community Health Workers (CHW) work, individually or collectively, in disease prevention and health promotion activities. These professionals are responsible for increasing the link between patients and the community with the Primary Healthcare. Therefore, the CHW were chosen for this research because they are directly involved in efforts to control tuberculosis, among which includes the DOT. This is a cross-sectional study conducted by semi-structured, self-administered and pre-tested questionnaire applied in a random and representative sample of 489 professionals in Belo Horizonte, MG. The measure variables were arranged in levels of knowledge about tuberculosis control measures and DOT. After analyzing, the knowledge level was categorized as below or above the median for comparison of the explanatory characteristics. There was a predominance of female respondents, aged between 30 and 39 years, high school completed and working for three years or more. With regard to knowledge, the average was 74.6%, demonstrating that CHW dominate what should be their actions in the management of tuberculosis cases. However, there was a gap in knowledge about the identification of patients with active tuberculosis, the target audience of the DOT and what the proper technique for treatment supervision. Association was observed between increased knowledge and follow-up of cases in the 12 months preceding the interview, training in tuberculosis and level of education. This study may help to construct strategies aimed at improving the professional practice of CHW and improvement of TB control activities